CD44 immunoreactivity in the developing human kidney: a marker of renal progenitor stem cells?. (August 2013) - Fanni, Daniela; Fanos, Vassilios; Gerosa, Clara; Senes, Giancarlo; Sanna, Alice; Van Eyken, Peter; Iacovidou, Nicoletta; Monga, Guido; Faa, Gavino
Abstract CD44 is a transmembrane adhesion glycoprotein, functioning as a hyaluronan receptor and participating in the uptake and degradation of hyaluronan. Recently, CD44 has been proposed in the adult kidney as a marker of activated glomerular parietal epithelial cells, the putative niche stem cells that, in case of damage to podocytes, might migrate inside the glomerular tuft and undergo transition to podocytes. Here, immunoreactivity for CD44 was tested in 18 human fetuses and newborns with a gestational age ranging from 11 to 39 weeks. CD44 immunoreactivity was observed in all but one developing kidneys, being localized in several renal cell types including intraglomerular, capsular, cortical and medullary interstitial cells and nerve cells. In some cases, CD44 marked scattered cells in nephrogenic subcapsular zone. Our data indicate that CD44 is involved in human nephrogenesis, probably marking a subset of progenitor/stem cells involved in early phases of kidney development and, putatively, in podocyte and/or interstitial cell differentiation.